A Biomechanical Comparison of Fixation Techniques in Metacarpal Shaft Fractures - Albanese, Kevin M.; Schreck, Michael J.; Werner, Frederick W.; Esper, Garrett W.; Ordway, Nathaniel R. (Journal of Wrist Surgery, 2022)
Background Typically, metacarpal shaft fractures are treated with closed reduction percutaneous pinning, intramedullary nails, or plate fixation. Recently some surgeons have begun using intramedullary headless compression screws.Questions/Purposes The purpose of this study was to compare intramedullary screw fixation to K-wire fixation, which is the standard of care in a transverse metacarpal midshaft fracture, using a cadaveric model. Our hypothesis was that intramedullary screw fixation would have a biomechanical advantage (higher stiffness and peak load to failure) when compared with dual Kirschner wire fixation of transverse metacarpal shaft fractures.Methods Four-point bend testing was performed to compare stiffness and failure load values of seven paired 2nd and 3rd metacarpals instrumented with headless intramedullary compression screw fixation or Kirschner wire fixation. Similar testing was performed on 14 unpaired 4th metacarpals.Results There was no significant difference in peak load (p = 0.60) or stiffness (p = 0.85) between fixation groups for the 2nd and 3rd instrumented metacarpals. For the instrumented 4th metacarpals, there was no significant difference in peak load (p = 0.14), but the stiffness was significantly greater (p = 0.01) for the compression screw group compared with the Kirschner wire fixation.Conclusions/Clinical Relevance In this study, the load to failure was not different between the two fixation methods and likely both techniques can sustain physiologic loads needed for rehabilitation. The greater stiffness in the 4th metacarpal compression screw group may be related to the smaller canal morphology than in the 2nd and 3rd metacarpals. Larger diameter screws may be needed to obtain a better fit particularly in the 2nd and 3rd metacarpals.
Keywords: metacarpal fractures; intramedullary; headless compression screw; Kirschner wire